Inheritance Law Interpretation in Sunni and Shia: A Cross-Madzhab SDGs Perspective - Kerwanto (Profetika: Jurnal Studi Islam, 2025)
Objectives: This study aims to compare Sunni and Shia interpretations of Qur'anic verses on inheritance, focusing on the concepts of ‘ashabah (Sunni) and qarābah (Shia). It explores how these interpretations influence inheritance rights and the order of heirs, and examines their alignment with modern concepts of justice and equality, particularly in the context of the Sustainable Development Goals (SDGs). Theoretical framework: The study analyzes Sunni and Shia jurisprudence on inheritance, connecting these interpretations with contemporary ideals of justice, equality, and the SDGs. Literature review: The review examines classical and modern perspectives on Qur'anic inheritance verses, highlighting gender and justice issues in Sunni and Shia law. Method: Using a qualitative approach, the study compares Sunni and Shia legal texts to explore their interpretations of inheritance laws and contemporary ethical concerns. Result: The study finds that Sunni inheritance law follows a patrilineal structure, prioritizing male heirs, while Shia law is more inclusive, valuing blood relations regardless of gender. This highlights different legal approaches to inheritance in both traditions. Implications: The findings suggest a need to reinterpret Islamic inheritance laws to better align with gender equality and modern justice principles, especially the SDGs. Novelty: This study offers a new comparative analysis of Sunni and Shia inheritance laws, linking them to contemporary issues like gender equality and justice.